Analisis Kesalahan Siswa Dalam Menyelesaikan Masalah Polinomial di SMP Negeri 10 Kota Ternate - Jumrati Sangaji; Dana Arif Lukmana (Peneliti.net, 2023)
The purpose of this study was to find out the types of mistakes made by students in solving polynomial problems. The type of research conducted is descriptive quantitative. With research subjects 17 students of class VIII but who took the test 14 students. The instrument questions used are test questions in the form of 4 essay questions. Based on data analysis, there are three types of errors in solving polynomial problems, namely 1) systematic errors in addition with a percentage of 42.85%, subtraction with a percentage of 50%, multiplication with a percentage of 21.42% and word problems with a percentage of 50%, random errors in addition with a percentage of 28.57%, subtraction of 35.71%, multiplication with a percentage of 71.42% and carelessness errors with a percentage of 14.28%, multiplication with a percentage of 7.14% and word problems with a percentage of 50%.